Integrated Disease Management Practices for Resilient Rice Production in Dakshina Kannada District of Coastal Karnataka - Kedarnath; Ramesha, T. J.; Lingappa, Mallikarjuna; Shenoy, Harish; Reddy, Rashmi; Narayana, Chethan; Koute, Ashwini S.; Kumara, Rathod (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during kharif (June, 2022 to November, 2022 and June, 2023 to November, 2023) in farmers’ fields at Ichlampady village of Puttur taluk and Kella Puttige of Moodbidre taluk, Dakshina Kannada district, Karnataka. The present study aimed to demonstrate the integrated disease management practices such as summer deep ploughing followed by soil application of agriculture lime at 200 kg acre-1 before 15 days of transplantation; application of farm yard manure at 4 t acre-1 7 days before transplanting; recommended dose of fertiliser application; seed treatment with carbendazim 63%+mancozeb 12% 75wp at 4 g kg-1 seeds; foliar application of carbendazim 50% wp at 1 g l-1 of water during 25th and 40th days after transplanting; application of tricyclazole 75% wp at 0.6 g l-1 of water during flowering were demonstrated against blast and brown spot diseases under natural infection. The integrated disease management practices showed most effective in controlling leaf blast, panicle blast and brown spot diseases, leading to 76.38%, 67.73% and 67.75% reduction respectively over farmers practice. The economic analysis revealed that integrated disease management practices achieved higher net return (` 61,675 ha-1) with higher benefit cost ratio (1:2.88) as compared to farmer practice (1:1.55). The demonstration study recorded a technology gap of 1.09 t ha-1, extension gap of 0.98 t ha-1 and a technology index of 21.74%. The present study highlighted that, IDM practices were feasible and economically viable over farmers practices, offering a superior option for controlling rice diseases.